Stimulation of Naturalistic and Kinesthetic Intelligence Through Exploratory Activities in the Surrounding Environment of Early Childhood - Evy Fitria; Nurfazriyah Nurfazriyah; Desi Ashari Ashari; Yani Oktapiyani (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This research addresses the critical need to implement the School Religious Culture program during early childhood to cultivate noble character through daily activities. The study utilized a qualitative approach at TKN Pembina Wlingi through interviews, observation, and documentation, focusing on: (1) program implementation, (2) supporting and inhibiting factors, and (3) strategies for factor management. The findings confirm that the School Religious Culture program successfully develops the noble character of early childhood children, producing individuals who are more positive, religious, and morally upright. This success is strongly supported by the principal, teachers, educational staff, and parents, who continuously strive to instill religious character through consistent, non-pressurized daily habituation.